Accounting-based measures of financial performance and risk disclosure of ACE Market Listed Companies / Rina Fadhilah Ismail and Nik Mohamad Nizam Mohd Kamil - Ismail, Rina Fadhilah; Mohd Kamil, Nik Mohamad Nizam (Faculty of Accountancy, 2019)
Past studies highlight the important of business decisions as regard to risk events occurred or expected to be occurred in current business landscape in the annual reports. Extensive risk information would be a signal of managers’ actions that may influence the investment decision by the investors. As the financial performance of the companies can be an indication of companies’ financial health, utilizing this financial performance would be a good determinant in determining manager’s decision in disclosing risk information. Hence, this study attempts to examine the relationship between the financial performance with risk disclosure among ACE Market listed companies. Using a sample of 261 companies listed under ACE Market in Bursa Malaysia covering three - year periods from 2014 until 2016, this study employs a quantitative method and content analysis to meet the objective of the study. Accounting - based measures and market - based measures of financial performance (i.e return on assets, return on equity, return on sales, return on capital employed, and market – to - book) are used as proxies for financial performance that expected to influence the risk disclosure. The findings observed that the risk disclosure practice among ACE Market PLCs is still at a moderate level whereby most companies more inclined to disclose mandatory risk instead of voluntary risk disclosure. Furthermore, the regression results showed significant relationships between the return on sales and market – to - book toward risk disclosure. While other p roxies do not indicate significant influences towards risk disclosure. Thus, findings are useful to the stakeholders and researchers in assessing managers’ behaviour towards decision to disclose or not the risk information particularly voluntary aspect of it.